2020
DOI: 10.1002/adsc.202001269
|View full text |Cite
|
Sign up to set email alerts
|

Boron‐Catalyzed Dehydrative Friedel‐Crafts Alkylation of Arenes Using β‐Hydroxyl Ketone as MVK Precursor

Abstract: Boron‐catalyzed environmentally benign dehydrative Friedel‐Crafts alkylation of indole/pyrrole and aniline derivatives with β‐hydroxyl ketones has been developed for the first time. This method provides an efficient and green replacement of toxic and unstable methyl vinyl ketone (MVK) by safer and cheaper β‐hydroxyl ketone. The reaction features easy operation, wide substrate scope and significantly, only water is formed as by‐product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…16 Fu and Shang et al reported a visible-light-induced Minisci-type reaction via a three-component EDA complex, which was derived from a catalytic amount of sodium iodide and triphenylphosphine with stoichiometric redox-active esters (Scheme 1c). 16c Owing to the importance of C−S structural motifs, 17 and based on our interest in the transformation of indoles, 18 we speculated that electron-poor B(C 6 F 5 ) 3 can form an EDA complex with electron-rich indole compounds, and the indole radicals formed by photoinduced SET can be cross-coupled with sulfur radicals to realize the aerobic sulfenylation (Scheme 1d). We commenced our study with 2-phenylindole 1a (1 equiv) and 4-(tert-butyl)benzenethiol 2a (1.2 equiv) as the model substrates.…”
mentioning
confidence: 99%
“…16 Fu and Shang et al reported a visible-light-induced Minisci-type reaction via a three-component EDA complex, which was derived from a catalytic amount of sodium iodide and triphenylphosphine with stoichiometric redox-active esters (Scheme 1c). 16c Owing to the importance of C−S structural motifs, 17 and based on our interest in the transformation of indoles, 18 we speculated that electron-poor B(C 6 F 5 ) 3 can form an EDA complex with electron-rich indole compounds, and the indole radicals formed by photoinduced SET can be cross-coupled with sulfur radicals to realize the aerobic sulfenylation (Scheme 1d). We commenced our study with 2-phenylindole 1a (1 equiv) and 4-(tert-butyl)benzenethiol 2a (1.2 equiv) as the model substrates.…”
mentioning
confidence: 99%
“…70 Moreover, dehydrative Friedel-Craft alkylation of indoles with β-hydroxy ketones has also been developed in the presence of a B(C 6 F 5 ) 3 catalyst (Scheme 1c). 71 Herein, we demonstrate B(C 6 F 5 ) 3 catalyzed dehydrogenative sequential C-C/C-C bond formation of indoles with N-tosylhydrazones of aryl aldehydes and ketones for the formation of bioactive DIMs under mild conditions (Scheme 1d). Although the synthesis of DIMs has been well established under metal-free conditions, it should be noted that access to unsymmetrical DIMs is still challenging.…”
Section: Introductionmentioning
confidence: 95%
“…Most importantly, regioselective C3 alkylation of indoles by C-C bond formation that leads to omnipresent bioactive indole derivatives has recently been demonstrated in the presence of a B(C 6 F 5 ) 3 catalyst (Scheme 1). [69][70][71] Very recently, Melen et al have reported B(C 6 F 5 ) 3 catalyzed highly regioselective C3 alkylation of indoles with α-aryl α-diazoesters via C-H insertion (Scheme 1a). 69 Similarly, Pulis et al have shown boron-catalyzed direct C3 alkylation of indoles with amine based alkylating agents (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the 50% diastereomeric excess of (M,P)bis [7]H obtained by solution synthesis, the diastereomeric excess of (M,P)-bis [7]H produced by the on-surface Ullman coupling of Br [7]H is about 74.6 ± 5%, indicating that a surface may induce diastereoselectivity by topochemistry. Friedel−Crafts (F−C) alkylation of aromatic and heteroaromatic compounds, in which a hydrogen atom is replaced by an alkyl group is a classical and useful C−C bond coupling reaction in organic and industrial chemistry for the synthesis of aromatic polymers, 37 important synthetic intermediates, 38,39 and catalytic asymmetric products, 30,40 which has been extensively studied in solutions. For example, Cui et al 37 achieved the synthesis of novel porous aromatic framework materials with tetrahedral-structured tetraphenylsilane as the monomer through the F−C alkylation reaction catalyzed by anhydrous FeCl 3 under mild conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Friedel–Crafts (F–C) alkylation of aromatic and heteroaromatic compounds, in which a hydrogen atom is replaced by an alkyl group is a classical and useful C–C bond coupling reaction in organic and industrial chemistry for the synthesis of aromatic polymers, important synthetic intermediates, , and catalytic asymmetric products, , which has been extensively studied in solutions. For example, Cui et al achieved the synthesis of novel porous aromatic framework materials with tetrahedral-structured tetraphenylsilane as the monomer through the F–C alkylation reaction catalyzed by anhydrous FeCl 3 under mild conditions.…”
Section: Introductionmentioning
confidence: 99%